2015
DOI: 10.1080/09540253.2015.1027669
|View full text |Cite
|
Sign up to set email alerts
|

Diverse experiences of women leading in higher education: locating networks and agency for leadership within a university context in Papua New Guinea

Abstract: The ways in which women deliberately press back against practices of oppression and demonstrate agency in higher education institutions are highly contextual and culturally bound. The formal and informal networks that women develop and maintain are important elements of generating agency and enhancing women's access to and opportunities for leadership. This article presents a case study from research that explored women's leadership experiences in a higher education context in the Pacific Islands -Papua New Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Addi-Raccah and Ayalon (2002) found that teaching had become a female occupation while men retain dominant leadership positions. Similarly, McNae and Vali noticed “women’s overrepresentation in the teaching population, and their under-representation in educational leadership positions” (McNae and Vali, 2015: 288). Lennon (2012) found that in America’s higher education, 57% of students were females.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Addi-Raccah and Ayalon (2002) found that teaching had become a female occupation while men retain dominant leadership positions. Similarly, McNae and Vali noticed “women’s overrepresentation in the teaching population, and their under-representation in educational leadership positions” (McNae and Vali, 2015: 288). Lennon (2012) found that in America’s higher education, 57% of students were females.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Moreover, their participants were frequently representatives of the white middle-class (Wilkinson, 2009). Only recently has the field been enriched with studies shedding light on the East Asian (e.g., McNae and Vali, 2015; Morley, 2014; Morley and Crossouard, 2016; Nguyen et al, 2012), the South African (e.g., Obers, 2015) and the Middle Eastern experiences (e.g., Arar and Oplatka, 2016; Morley, 2014; Samier, 2015). To our knowledge, no studies have yet been conducted on women in Central Asian academia.…”
Section: Review Of the Western Research On Females In Academic Leadermentioning
confidence: 99%
“…To achieve greater gender equality in university leadership, it is important to understand better how females in academia progress towards leadership and what their experiences as leaders are. While many studies have recently been conducted on the topic (see, for example, Acker, 2012, 2014; Airini et al, 2011; Aiston, 2014; Morley, 2014; Morley and Crossouard, 2016; McNae and Vali, 2015; Obers, 2015; Wallace and Marchant, 2009), most of the prior research has been ‘constructed, classified, and theorized from a white hegemonic perspective’ (McNae and Vali, 2015: 289), which has led to homogenization, marginalization and silencing of women educational leaders from non-Western countries (Fitzgerald, 2006). More studies of female experiences as academic leaders in various cultural contexts are necessary to explain women’s leadership experiences in non-Western contexts (Fitzgerald, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This process we concluded from our synthesis of the literature 'is strongly enabled through its [TE's] participation within collaborative relationships and partnerships that are facilitated through its teaching and learning and engagement functions' (Howell, Unterhalter and Oketch 2020, p 5). These included the strengthening of TE institutions themselves through partnerships or networks with other TE institutions or research bodies (Cloete, Bailey and Pillay, 2011;Allen 2014;Johnson et al 2011;Amare 2017;McNae and Vali 2015), with different levels or structures of government (Magara et al 2011;Situmorang et al 2018) and with employers or industry partners (Kirby 2019). Other examples noted the involvement of students in internships with community organisations involving knowledge transfer (Magara et al 2011) and the engagement of TE with local economic development strategies (Fongwa and Wangene-Ouma 2015).…”
Section: Tertiary Education and The Implementation Of The Sdgs: Undermentioning
confidence: 99%